Cloud enterprise resource planning selection model for small and medium enterprises - Ogunrinde, Rowland R.; Jusoh, Yusmadi Yah; Che Pa, Noraini; Wan Ab. Rahman, Wan Nurhayati; Abdullah, Azizol (American Scientific Publishers, 2016)
Enterprise Resource Planning (ERP) systems automate and integrate business management activities thereby aiding the organization achieve operational excellence and competitive advantage. However, traditional ERP has been observed to be too costly for most Small and Medium Enterprises (SMEs) which are known to be the economic agents of rural development globally. Emergence of Cloud computing offers the SMEs opportunities of accessing cloud-hosted infrastructure to evade huge initial capital. As there are myriads of providers offering ERP as Software-as-a-Service (SaaS), there arises the challenge as per choosing a provider with Quality of Service (QoS) that would be suitable to meet the organizations’ customized requirements. The paper presents a model which not only seeks to address this challenge, the model goes a step further to select the most affordable among a selected few providers that are suitable for the SMEs to keep them agile and competitive.